Investigating the Types and Strategies of Expressive Illocutionary Acts - et. al., Ida Zuraida Supri, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to identify the types, the strategies and the functions of expressive illocutionary acts employed in The Longest Ride movie by George Tillman. The method used in this study is a qualitative descriptive method. The results of this study indicate that from 30 data analyzed: 1) the six types of expressive illocutionary acts are found with the following description: expressive illocutionary act thanking 12 data (40%), expressive illocutionary act congratulating 1 data (3%), expressive illocutionary act pardoning 3 data (10%), expressive illocutionary act blaming 1 data (3%), expressive illocutionary act praising 10 data (34%), and expressive illocutionary act condoling 3 data (10%). 2) there are two types of speech act strategies, namely: direct speech act 29 data (97%) and indirect speech act 1 data (3%)